2017
DOI: 10.4038/cmj.v62i1.8433
|View full text |Cite
|
Sign up to set email alerts
|

Body image construct of Sri Lankan adolescents

Abstract: Introduction "Body image" is more than the visual perception of size and it is probably multidimensional. It is known to influence eating behaviors and self-esteem of adolescents.Although widely studied in developed countries, it has been studied little in Sri Lanka.Objectives This study was designed to translate and culturally adapt a tool to assess dimensions of body image in Sri Lankan adolescents. MethodsThe study was carried out in the Anuradhapura District on school going children in grades nine to eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…In this study, among the study subjects corresponding to the low quartile of quality of life, those who recognized that excessive weight control was necessary due to distorted body perception showed lower quality of life in mental health, daily life, sexual relations, and work–process balance. This is consistent with several studies [ 22 , 23 ] stating that distorted body perception reflects negative psychological states such as unhealthy behavior and diet, low self-esteem, and suicidal thoughts, and was confirmed as an influencing factor for low quality of life.…”
Section: Introductionsupporting
confidence: 92%
“…In this study, among the study subjects corresponding to the low quartile of quality of life, those who recognized that excessive weight control was necessary due to distorted body perception showed lower quality of life in mental health, daily life, sexual relations, and work–process balance. This is consistent with several studies [ 22 , 23 ] stating that distorted body perception reflects negative psychological states such as unhealthy behavior and diet, low self-esteem, and suicidal thoughts, and was confirmed as an influencing factor for low quality of life.…”
Section: Introductionsupporting
confidence: 92%
“…Sohrabi et al [ 13 ] categorized the body image perception of pregnant women into three categories: symbols from motherhood and vulnerability; feelings towards changes in the body derived from negative feelings towards changes in the skin; unfit, ridiculous-obsessed shape and attention-seeking shape of the body; and attraction category from sexual with beauty attractions. Additionally, Goonapienuwala et al [ 14 ] and Voelker et al [ 15 ] averred that body image, as a multifaceted construct, includes perceptual, cognitive, and affective components regarding one’s own body as well as the bodies of others. Fahami et al [ 16 ] and Plante et al [ 17 ] concluded that women are dissatisfied with their body image, especially in the third trimester, when all parts of the body are affected.…”
Section: Introductionmentioning
confidence: 99%
“…1 Dietary habits of young people is found to be a multidimensional public health issue that encompasses socio-cultural beliefs about foods, affordability and availability of healthy foods, body image and eating disorders. [1][2][3][4][5] Even though the relationship between diet and health is clear, and many countries have introduced and implemented health promotion campaigns for healthier eating, most young peoples' dietary habits are poor. [5][6][7][8][9] Diet and food preferences of young people are largely determined by social, economic, environmental and cultural factors than by their concern for health.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Even though the relationship between diet and health is clear, and many countries have introduced and implemented health promotion campaigns for healthier eating, most young peoples' dietary habits are poor. [5][6][7][8][9] Diet and food preferences of young people are largely determined by social, economic, environmental and cultural factors than by their concern for health. [1][2][3] Although traditional Sri Lankan diet contains plenty of vegetables and rise, dietary behaviors' of Sri Lankan's have been changed drastically during the last few decades as a result of socio-cultural, epidemiological, demographic and economical transitions occurred in the country during that period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation